Genomic landscape of ground glass opacities (GGOs) in East Asians - Cao, Peng (J Thorac Dis, 2021)
BACKGROUND: Understanding the genomic landscape of early-stage lung adenocarcinoma (LUAD) may provide new insights into the molecular evolution in the early stages of LUAD. METHODS: Through sequencing of 79 spatially distinct regions from 37 patients with ground glass opacities (GGOs), we provided a comprehensive mutational landscape of GGOs, highlighting the importance of ancestry differences. RESULTS: Our study had several interesting features. First, epidermal growth factor receptor (EGFR), BRAF (v-RAF murine sarcoma viral oncogene homologue B1), and ERBB2 (Erb-B2 Receptor Tyrosine Kinase 2, also known as HER2) were more frequently mutated in our study, which supports the notion that EGFR is considered to be a major driver and tends to drive the occurrence of LUAD. Second, Signature 1, Signature 3, and Signature 6 were identified in patients with GGOs. Our results further suggested that Signature 1 was more prominent among early mutations. Third, compared with LUADs, GGOs exhibited significantly lower levers of arm-level copy number variation (CNV)—which alter the diploid status of DNA, and lower focal CNVs. CONCLUSIONS: In our study, 79 samples of patients were included to analyze the GGO gene profile, revealing the genetic heterogeneity of GGO in East Asian population, and providing guidance for prognosis analysis of GGO patients by comparison with LUAD. Our study revealed that GGOs had fewer genomic alterations and simpler genomic profiles than LUADs. The most commonly altered processes were related to the receptor tyrosine kinase (RTK)/Ras/phosphatidylinositol-3-kinase (PI3K) signaling pathways in GGOs, and EGFR alterations were the dominant genetic changes across all targetable somatic changes.